The economic problem - Heilbroner, Robert L. (Englewood Cliffs, N.J. : Prentice-Hall, 1970)
The trouble with economics is that it will not stand still. issues change, ideas change, understanding changes. Even the past does not look exactly the same from one year to the next, and the present is apt to alter almost out of all recognition.
Includes index.
Includes bibliographical references.
II 17/01/2019
Loans
Keywords: Economics